2021
DOI: 10.1001/jama.2021.6128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Implantable vs Prolonged External Electrocardiographic Monitoring on Atrial Fibrillation Detection in Patients With Ischemic Stroke

Abstract: The relative rates of detection of atrial fibrillation (AF) or atrial flutter from evaluating patients with prolonged electrocardiographic monitoring with an external loop recorder or implantable loop recorder after an ischemic stroke are unknown.OBJECTIVE To determine, in patients with a recent ischemic stroke, whether 12 months of implantable loop recorder monitoring detects more occurrences of AF compared with conventional external loop recorder monitoring for 30 days. Investigator-initiated, open-label, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 23 publications
(40 reference statements)
5
106
3
2
Order By: Relevance
“…Of these, a total of 710 articles were excluded due to duplication and irrelevance and 119 full articles were further assessed for eligibility; subsequently, 116 articles, including 28 non-randomized clinical trials, seven case reports, five meta-analyses, and 76 reviews. Eventually, three RCTs [18][19][20] containing 1233 patients (613 in the ICM group and 620 placebo group) were selected for qualitative synthesis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, a total of 710 articles were excluded due to duplication and irrelevance and 119 full articles were further assessed for eligibility; subsequently, 116 articles, including 28 non-randomized clinical trials, seven case reports, five meta-analyses, and 76 reviews. Eventually, three RCTs [18][19][20] containing 1233 patients (613 in the ICM group and 620 placebo group) were selected for qualitative synthesis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…One RCT was excluded in Fig. 2C due to offering insufficient data of the time to first detection of AF within 12 months [20].…”
Section: Efficacy Outcomementioning
confidence: 99%
“…Implantable loop-recorder (ILR) is considered safe and provides excellent long-term observation due to automatic reporting with little discomfort to the patients. It is superior to long-term wearable monitors in the detection of AFib in non-cardioembolic stroke (7). Previous studies showed AFib detection after long-term observation in up to 30% of patients after cryptogenic stroke (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in wearable stretch sensors has increased due to their potential uses in medical applications to monitor the health of a patient [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ], to assess biomechanics, [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], and as drug delivery systems in pharmaceutical applications [ 22 , 23 ]. Wearable sensors may also have applications in athletics.…”
Section: Introductionmentioning
confidence: 99%